THE IMPACT OF POVERTY ALLEVIATION PROGRAMS ON POVERTY AT DISTRICT LEVEL IN INDONESIA: CASE STUDY OF SLEMAN, 2008-2012 - Kurniawan, Kharis Fadlan Borni; Kuncoro, Mudrajad (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2016)
The economic crisis of 1997/1998 greatly affected the national economy of Indonesia by making more people vulnerable to the poverty. To tackle the problems of poverty, Indonesian government has issued some poverty alleviation programs and strategies through national and local budget allocations. The national government has set up some poverty reduction programs, including The National Program for Community Empowerment (Program Nasional Pemberdayaan Masyarakat/PNPM). Beside PNPM, there is a program of Alokasi Dana Desa/ADD that comes from the district budget (local funding). In terms of budget allocation, both central and local government has always increased their support from year to year. This study examines the impact of poverty alleviation programs, including BLM PNPM and ADD on poverty at district level in Indonesia with the case study of Sleman district in Yogyakarta province during 2008-2012. Using trend analysis, Klassen typology and pooled least square analysis, this study generally finds that the poverty alleviation programs do not significantly reduce the level of poverty in Sleman.